2021
DOI: 10.1001/jamanetworkopen.2021.24938
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance for Colonization, Transmission, and Infection With Methicillin-Susceptible Staphylococcus aureus in a Neonatal Intensive Care Unit

Abstract: Key Points Question What are the risk factors for the acquisition of methicillin-susceptible Staphylococcus aureus (MSSA) colonization and infections in a neonatal intensive care unit? Findings In this cohort study of 590 newborns, the acquisition of S aureus colonization and infection was monitored until hospital discharge. Colonization with MSSA was associated with lower birth weight, longer hospitaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 41 publications
(112 reference statements)
0
24
1
5
Order By: Relevance
“…The finding indicates that most patients were at risk of contracting ESBL-PE infections during their course of admission to the ICU. As previous studies have shown, colonization with resistant bacteria is the pre-request for subsequent infections [ 3 , 31 ]. On the other hand, the high carriage we have observed in these patients at admission indicates a high risk of spreading ESBL-PE to other patients admitted to the ICU.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The finding indicates that most patients were at risk of contracting ESBL-PE infections during their course of admission to the ICU. As previous studies have shown, colonization with resistant bacteria is the pre-request for subsequent infections [ 3 , 31 ]. On the other hand, the high carriage we have observed in these patients at admission indicates a high risk of spreading ESBL-PE to other patients admitted to the ICU.…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotic use exerts selective pressure leading to the overgrowth of resistant bacterial populations (endogenous colonization). Theoretically, colonization of patients with these pathogens is the prerequisite for subsequent invasive disease [ 3 ], and infections in ICU result in significant morbidity, mortality, and high healthcare costs [ 2 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As sequencing capacity and expertise within the clinical realm continues to expand, it is interesting to reflect on whether near real-time availability of sequencing results would have enabled establishment of transmission routes with greater certainty, and afforded the opportunity to reduce or eliminate the transmission risk. A recent study of Staphylococcus aureus infection and colonization within a German neonatal unit similarly showed evidence of frequent transmission events occurring in spite of regular screening and enhanced infection prevention and control measures [26].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in pediatric patients have thus far focused mostly on determining S. aureus- and MRSA-colonization rates, especially in patients receiving care in the neonatal intensive care environment as well as pre-operatively [ 8 , 9 ]. Studies evaluating MNS in children admitted for presumed infectious disease diagnoses are lacking.…”
Section: Introductionmentioning
confidence: 99%